Analysis of Strength Parameter of Cement Concrete using GGBS and Coconut Shell Powder - Nandini K., Divya A., Md. Rahil Azam (International Journal of Advanced Science and Technology, 2020)
As all we know that the impacts from the various cement industries to the environment. Major impact is Global warming and Greenhouse gas effect due to emission of toxic chemicals from cement industries. To reduce or to overcome from these impact of the industrial wastes the various replacement materials like GGBS, FLYASH, RICE HUSK, SILICA FUMES etc. are considered. In the present study we are using GGBS and Coconut shell powder (CSP) as replacement material in various percentages with Cement in M40 grade of concrete and we have casted Cubes, Cylinder and Beams to determine Compression, Tensile, Flexural and Thermal Compressive Strength. The specimens are cured for the period of 7, 14 and 28 days. The main concentration of research is to enhance the strength parameter of M40 grade of concrete in which cement is replaced by GGBS and CSP in 10, 20, 30 and 40 % and 1, 3 and 5% respectively and also the thermal behavior of compression specimens of GGBS and CSP replaced M40 concrete at elevated temperature. From the test results it is concluded that increasing percentage of GGBS and CSP with cement increases the compressive, split tensile and flexural strength with increasing period of curing. GGBS content of 20% and 3% of CSP achieves higher strength and the thermal compressive strength at elevated temperature of 90°C for 28days of curing.